Experiences of Rangatahi Māori with Mental Health Services in Aotearoa - Rihari, Teina (Auckland University of Technology, 2022)
Currently, there is a distinct lack of research on rangatahi Māori and mental healthcare in Aotearoa. Research on mental healthcare in Aotearoa has predominantly explored Pakeha and adult experiences. This present research pursued to fill this gap in the literature by investigating the experiences of rangatahi Māori with experiences with mental healthcare in Aotearoa. From these interviews, information will be extracted to add to the limited available research and uncover prospective topics for future research with rangatahi Māori. Māori-centric qualitative methodology was employed in the current study. Data was collected through semi-structured interviews with rangatahi Māori who have experiences with mental healthcare in Aotearoa. Thematic analysis was used to examine the data collected. Two overarching themes were identified: barriers and enablers. These overarching themes comprise eight emergent themes: 1a) Health literacy, 1b) Stigmatism, 1c) Time, 1d) Financial and socioeconomic factors, 2a) Whakawhānaungatanga, 2b) Transparency, 2c) Satisfaction with service, 2d) Incorporation of Māori culture/models. The findings from these themes provided recommendations for service providers and future research into rangatahi Māori mental health